2022
DOI: 10.1177/10547738221075726
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application Value of Multimedia Education and Nursing Intervention in a Coronary Computed Tomography Angiography

Abstract: To explore the application value of multimedia education and nursing intervention in a coronary computed tomography angiography (CCTA). A total of 120 patients who underwent a 256-slice spiral CCTA examination in our hospital from April 2019 to April 2020 were selected. Patients were divided into two groups of 60 patients each, that is, the control group and the observation group, using a random number table method. The control group received traditional education before an examination, and patients were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…121 This randomised trial provided novel information, as no previous studies on the effect of a 360 environment on anxiety among adult CCTA patients were found. The results demonstrate that access to the 360 VCE reduces CCTA patients' pre-CCTA levels of anxiety, which agreed with previous research on pre-CCTA multimedia education 11 and VR counselling. 51,52,106 However, it should be noted that earlier RCT studies 51,52,107 have focused on paediatric patients and used different scales; this makes any between-study comparisons difficult.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…121 This randomised trial provided novel information, as no previous studies on the effect of a 360 environment on anxiety among adult CCTA patients were found. The results demonstrate that access to the 360 VCE reduces CCTA patients' pre-CCTA levels of anxiety, which agreed with previous research on pre-CCTA multimedia education 11 and VR counselling. 51,52,106 However, it should be noted that earlier RCT studies 51,52,107 have focused on paediatric patients and used different scales; this makes any between-study comparisons difficult.…”
Section: Discussionsupporting
confidence: 90%
“…This minimises motion artefacts, improves image resolution and reduces the radiation dose. 88e90 However, anxiety during CCTA can reduce patient safety, 11 the quality of the imaging experience 44 the image quality, as well as increase the radiation dose. 10,13 Hence, focusing on the quality of counselling could prevent pre-cancellations and repeated scans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations